IMPLICATURE IN HUGO FILM: THE APPLICATION OF RELEVANCE THEORY - RAHMAWATI, ELLY (Jurnal Ilmiah Mahasiswa FIB, 2014)
Rahmawati, Elly. 2014.  Implicature in Hugo Film: The Application Of Relevance Theory. Study Program of English, University of Brawijaya. Supervisor: Nurul Chojimah; Co-supervisor: Tantri Refa IndhiartiKeywords: implicature, relevance theory, Hugo filmCommunication is the way to interact between each other. To maintain a good communication, implicature as an intention behind utterances is very important to understand because if one of the participants does not know the true meaning, communication will not successfully happen. The researcher conducted a study about Implicature in “Hugo” film which shows the implicature occurring in the conversational of the character. In the study of implicature, the researcher use Relevance theory elaborating  the explicit content and recovering the implicit message are equally important to understand the intended meaning. There  are three problems  in the study to be solved, namely: (1) What is the explicature conveyed in the utterances of “Hugo” Film,  (2) What  are implicated premises conveyed in the utterances of “Hugo” film, (3) What is the implicated conclusion conveyed in the utterances found in “Hugo” film.   In this study  qualitative approach  as applied  in which  the data were collected in the form of words or sentences and not in numerical scores. Content or document analysis is the research design, since the researcher analyzes the utterance that taken from Hugo film using content analysis design, which is a study tool focused on the actual content that is used to determine the presence of words. This study reveals that there are thirteen utterances conveying implicature uttered by the characters of "Hugo" film. Findings is to corroborate that Relevance theory is an insightful pragmatics resource for explain  addresser’s intentions, which offering plausible explanations of how communicative meaning is mentally processed by the addressee. The  researcher suggests  the next researchers who want continue this study to use different data sources and  the other theory of Implicature and for English Study Program  to  add  more  references  relating  to this topic  in order  the next researchers could present rich literature review that is able to support the analysis of their study.